2021
DOI: 10.1149/1945-7111/abe8be
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of ZrO2 during SNF Pyrochemical Reprocessing

Abstract: Reduction of ZrO 2 by lithium during electrolysis of LiCl-KCl-Li 2 O melt at 650°C was studied using a set of physicochemical methods of analysis. Influence of ZrO 2 in the space near a molybdenum cathode on the kinetics of the cathode process was established. Possible variations of the electrode reaction associated with the zirconium reduction were proposed. The appearance of ZrO 2 in the cathode space resulted in consumption of reduced lithium and in increase in the potential relaxation time of the molybdenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…On the other hand, according to the SEM EDX data, the reduction of ZrO 2 samples with lithium proceeds only to lithium zirconates and non-stoichiometric compounds ZrO and Zr 3 O. Similar results were obtained at the reduction of ZrO 2 samples with lithium in the LiCl-KCl melt at the temperature of 650 °C, 20 where additional methods (nuclear microanalysis and alloying of reduced samples with tin) showed the absence of metallic zirconium in the samples. In our opinion, in the case of ICP analysis, the error can be caused by the dissolution of Zr 3 O in bromine-ethyl acetate, and in the case of XRD analysis, the fixed zirconium lines can actually refer to oxygen solutions in α-Zr present in the Zr-O system at relatively low temperatures.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…On the other hand, according to the SEM EDX data, the reduction of ZrO 2 samples with lithium proceeds only to lithium zirconates and non-stoichiometric compounds ZrO and Zr 3 O. Similar results were obtained at the reduction of ZrO 2 samples with lithium in the LiCl-KCl melt at the temperature of 650 °C, 20 where additional methods (nuclear microanalysis and alloying of reduced samples with tin) showed the absence of metallic zirconium in the samples. In our opinion, in the case of ICP analysis, the error can be caused by the dissolution of Zr 3 O in bromine-ethyl acetate, and in the case of XRD analysis, the fixed zirconium lines can actually refer to oxygen solutions in α-Zr present in the Zr-O system at relatively low temperatures.…”
Section: Resultssupporting
confidence: 68%
“…Thus, a special attention should be paid to the accurate determination of the oxide reduction degree during the pyrochemical reprocessing. In our previous work, 20 the reduction of ZrO 2 by lithium was studied during the LiCl-KCl-Li 2 O melt electrolysis at 650 °C. Using independent methods of analysis, it was revealed that the reduction of ZrO 2 by lithium proceeds only to lithium zirconate.…”
mentioning
confidence: 99%
“…, and kept at this temperature for 6 h. Purified K 2 SiF 6 was stored in a glove box and added to the chloride melt immediately before measurements. According to nuclear microanalysis data, 27 the oxygen content in the obtained K 2 SiF 6 did not exceed 0.2 wt%. All experiments were carried out with the content of K 2 SiF 6 3 wt%.…”
Section: Methodsmentioning
confidence: 87%
“…To verify this concept, a porous MgO crucible was used in this study (Figure b). MgO is highly stable in the chloride media and has been widely used as a structural material in the molten salt processes. , The HCIL-containing MgO crucible was stored inside the molten chloride salt at 700 °C and then recovered. The recovered MgO crucible remained stable after the experiment.…”
Section: Results and Discussionmentioning
confidence: 99%